Functional Analysis of Patients with Spinal Muscular Atrophy Based on Exploratory Item Response Theory Modeling - FAN Yabei; CHEN Jinjin; GE Panli; CHENG Xi; ZHANG Yichen; LIN Feng (康复学报)
ObjectiveBased on Hammersmith Function Motor Scale Expanded （HFMSE），the study aimed at constructing item response model （IRM） to evaluate the functioning of patients with spinal muscular atrophy （SMA） and exploring the metrical characteristics of HFMSE.MethodsWe recruited 23 SMA patients who received corrective treatment in the Department of Geriatric Neurology and the Department of Pediatrics of the First Affiliated Hospital with Nanjing Medical University from February 2021 to June 2023. IRM was constructed using these repeated measurement data based on stack design［1］. ，The comparisons between well-fitted models were based on likelihood ratio. And item guessing，carelessness，difficultyand personal abilities （θ） of selected optimal model were calculated. Differential test functioning （DTF） test was conducted for gender and rehabilitation therapy to test the bias. Monte Carlo simulation was used to prove that the item difficulty distribution of the model was not affected by the sampling process. And person-item plot was drawn according to the median expected difficulty. and the differences in the difficulty of each item in HFMSE scale and personal abilities among each evaluations were discussed.ResultsA total of 32items were included in this study and 4 alternative models were constructed. Three-parametric logistic model was selected as the optimal model with the best fitness （p > 0. 05，M2 statistics = 479. 75）. In 3PLM，the caution of all items was 1，and the discrimination，guessing and difficulty of the items were calculated. There were no DTFs for gender and rehabilitation therapy. The results showed high reliability （Cronbach's α = 0. 955，LCRC = 0. 981） and validity ［θ value is positively correlated with the original total score （P<0. 001，r = 0. 99）］ of 3PLM. There was conversion between personal abilities θ value and the total score of the scale：θ=-1. 63 + 0. 0651TTS－1. 39×10-5TTS2. A person-item plot showing the location of item parameters and individual parameters on the personal abilities （θ） scale was used to observe the relationship between θ values and item difficulties.ConclusionThe IRT model based on HFMSE offered a new approach to evaluate functional levels of SMA patients and difficulties of items. The calculation of item guessing，carelessness and difficulty of selected optimal model provides recommendations for better clinical practice of HFMSE. The study offers a new perspective for the assessment of the functions of SMA patients and guidance for the development of rehabilitation programs.